Sonochemical Functionalization of Boron Nitride Nanomaterials. (2020) - Harrison, Haley B.; Alston, Jeffrey R.
Abstract: Boron nitride nanotubes (BNNTs) and hexagonal boron nitride platelets (h-BNs) have received considerable attention for aerospace insulation applications due to their exceptional chemical and thermal stability. Presently, making BN nanomaterials compatible with polymer and composite matrices is challenging. Due to their inert and highly stable structure, h-BN and BNNTs are difficult to covalently functionalize. In this work, we present a novel sonochemical technique that enables covalent attachment of fluoroalkoxy substituents to the surface of BN nanomaterials in a controlled and metered process. Covalent functionalization is confirmed via colloidal stability analysis, FT-IR, and x-ray photoelectron spectroscopy (XPS).